2020
DOI: 10.1007/s10098-020-01941-9
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable enhancement of district heating and cooling configurations by combining thermal energy storage and life cycle assessment

Abstract: District heating and cooling systems are designed and optimized to respond to the latest challenges of reducing energy demands while fulfilling comfort standards. Thermal energy storage (TES) with phase change materials can be employed to reduce the energy demands of buildings. This study considers a residential district located in Spain, where a general framework has been established to identify optimal combinations of energy conversion, delivery technologies, and operating rules. The Life Cycle Assessment (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…In the configuration process, the configuration heat capacity (S WTES cap,i ) is usually related to the volume of the container [8,20]. In this article, it indicates the heat when the water tank is full of the upper temperature medium, representing the maximum heat storage quantity in theory.…”
Section: Water Thermal Energy Storagementioning
confidence: 99%
See 1 more Smart Citation
“…In the configuration process, the configuration heat capacity (S WTES cap,i ) is usually related to the volume of the container [8,20]. In this article, it indicates the heat when the water tank is full of the upper temperature medium, representing the maximum heat storage quantity in theory.…”
Section: Water Thermal Energy Storagementioning
confidence: 99%
“…During the period of wind curtailment, most of the heat supply tasks were undertaken by electric boilers and storage devices, so the wind power consumption space was improved. From the perspective of future planning, in [20], the authors proposed a configuration method with minimum emissions in the whole life cycle, considering the growth of heat load, climate warming, and other factors. A community in Spain was taken as a case to study the impact of a DTES system with a different design life.…”
Section: Introductionmentioning
confidence: 99%
“…The exergoenvironmental factor (f b,k ) is the ratio between non-exergy-related environmental impacts and the overall environmental impacts and indicates which type of impact is dominant. f b,k is calculated by Equation (13). (13) The LCA of natural gas was calculated with the aid of software SimaPro 9.1.1.1 [34], using the Ecoinvent 3.6 database [35] and Eco-indicator 99 (EI99) version 2.10 (within SimaPro).…”
Section: Exergoenvironmental Assessmentmentioning
confidence: 99%
“…The case study was developed in Mexico, and 80% GHG emission savings were obtained for the solar cooling system, along with an 85% and a 20% decreases in fossil fuel depletion and ecotoxicity, respectively. Spanish district heating and cooling systems were the focus of the LCAs in [13], whereby the authors studied different types of thermal energy storage and verified that the nonrenewable energy system always presented the highest emissions due to the consumption of fossil fuel (natural gas).…”
Section: Introductionmentioning
confidence: 99%
“…Aberilla et al (2020) conducted an LCA concerning energy systems and found that household-scale photovoltaic systems integrated with wind turbines and lithium-ion batteries in rural areas were the most environmentally friendly system of the systems they assessed. Guillén-Lambea et al (2020) did an LCA evaluating heating and cooling configurations and found that the environmental impact of the thermal energy storage system they researched was highly dependent on tank design. Corcelli et al (2019) found that in the Mediterranean, the SPR system had a smaller environmental impact than the RTG system, especially when considering climate change and fossil fuel consumption.…”
Section: Introductionmentioning
confidence: 99%